Biomechanics Measurements in Archery - Zulkifli, Ahmad; Zahari, Taha; Mohd Hasnun Ariff, Hassan; Mohd Azrul, Hisham; Nasrul Hadi, Johari; K., Kadirgama (Faculty Mechanical Engineering, UMP, 2014)
The purpose of this study is to measure the biomechanics parameter of the archery sports and correlate to the games performance. Archery becomes as one of the prospect sports to contribute medal in Olympics Games 2016. Therefore, the research in this sport is directly affected to the athlete performance during games tournament. This research is considered as preliminary study to measure the biomechanics parameters for applied to the professional athlete. The biomechanics parameter such as muscle activity, heartbeat, balancing and body posture as well as draw force line were chosen as important parameters related to the athletes performance. The subject was shooting the arrow on the force plate meanwhile the high speed video camera capturing the arrow velocity, body posture and elbow angle. Furthermore, those parameters will correlate to the point of target in order to propose the right technique for the player. The finding in this study will help the coach and athlete to improve the performance of the games, especially for the beginner level to become expert as an elite player.